The realization of child rights in Islamic boarding schools: A study of Al-Munawwir Krapyak Yogyakarta - Febiantoni, Fungki; Kusdarini, Eny; Fathurrahman, Ali Masykur; Azis, Sulthon Abdul; Hanum, Fathikah Fauziah (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2025)
Children are a key part of the future of a nation and state, as well as the continuity of human life. The government in Indonesia is responsible for protecting the rights of all children, including santri (students), through schools, including Islamic boarding schools (pesantren). The goal of this study is to look at how well the Al-Munawwir Islamic Boarding School in Krapyak, Yogyakarta protects the rights of children who are also students there. The research used a descriptive qualitative method and included santri, religious teachers (ustadz), and caretakers as participants. Data were gathered through interviews and written records, and then they were analysed by reducing, categorising, and unitising the data, presenting it, and drawing conclusions. The results show that, first, Al-Munawwir has followed the rules for protecting children and upholding their rights, especially the Convention on the Rights of the Child, which the Indonesian government has signed and made part of its national child protection laws. Second, small problems like bad behaviour by teens and not being able to fully protect rights because there are so many santri were found. These problems, on the other hand, did not stop children from getting their rights. Instead, they helped santri become more disciplined and focused in their religious studies. Third, the pesantren has dealt with these problems by taking both preventive and punitive steps to make the school a better place for everyone.